2022
DOI: 10.1017/brimp.2022.18
|View full text |Cite
|
Sign up to set email alerts
|

Adult experiences of constraint-induced movement therapy programmes: a qualitative study using the Theoretical Domains Framework and Capability, Opportunity, Motivation – Behaviour system

Abstract: Aim: To explore the experiences of adults who completed a constraint-induced movement therapy (CIMT) programme, and the barriers and enablers to their participation. Methods: Qualitative design using semi-structured interviews. Stroke and brain injury survivors (n = 45) who had completed CIMT as part of their usual rehabilitation were interviewed 1 month post-CIMT. Interviews were audio-recorded, transcribed and imported into Nvivo for analysis. Inductive coding was used to identify init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Similarly, the success of community‐based mCIMT programs relies on patient engagement and carer support (Stark et al, 2019). mCIMT is an intensive program that, despite its efficacy, can be challenging to complete (Borch et al, 2015; Christie et al, 2022). The perceptions and experiences of patients and carers who undertake or support a mCIMT program will be investigated in future research to understand the feasibility of the RITH mCIMT program.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the success of community‐based mCIMT programs relies on patient engagement and carer support (Stark et al, 2019). mCIMT is an intensive program that, despite its efficacy, can be challenging to complete (Borch et al, 2015; Christie et al, 2022). The perceptions and experiences of patients and carers who undertake or support a mCIMT program will be investigated in future research to understand the feasibility of the RITH mCIMT program.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of CIMT has not been universal, and numerous barriers to delivery are cited in the literature (15-17) as well as patient-identified barriers to participation (18). Specifically, the barriers to patient participation include the time commitment and intensity of CIMT, while enablers to completing a CIMT program include support from therapists, carers/supporters and seeing improvements in arm function (19). Recent research has shown that patients (n = 40) receiving either in-person or virtual CIMT were "highly satisfied" with CIMT overall and found it only "moderately difficult" to participate in, based on survey data (20).…”
Section: Introductionmentioning
confidence: 99%